2018
DOI: 10.1097/dcr.0000000000000945
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ileostomy Output Using Telemedicine: A Feasibility Trial

Abstract: Televideoconference evaluation is a feasible, reliable means of assessing ileostomy output with high patient and physician acceptance. Our pilot study provides rationale for further study in the postdischarge setting for patients with ileostomies. The incorporation of televideoconference assessment within a teledischarge program may enable early intervention to improve patient outcomes. See Video Abstract at http://links.lww.com/DCR/A455.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 18 publications
0
27
0
1
Order By: Relevance
“…The first was for preoperative assessment, diagnostic purposes, or for consultation with another surgical department ( 9 , 14 - 22 ). The second involved using telemedicine for postoperative wound assessment, from either a photograph of the surgical wound, via a health-monitoring machine, or an SMS from patients if they had an unusual symptom ( 23 - 31 ). The third used tele-monitoring in place of conventional clinics for follow-up ( 12 , 32 - 35 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first was for preoperative assessment, diagnostic purposes, or for consultation with another surgical department ( 9 , 14 - 22 ). The second involved using telemedicine for postoperative wound assessment, from either a photograph of the surgical wound, via a health-monitoring machine, or an SMS from patients if they had an unusual symptom ( 23 - 31 ). The third used tele-monitoring in place of conventional clinics for follow-up ( 12 , 32 - 35 ).…”
Section: Resultsmentioning
confidence: 99%
“…The third type of intervention was telemedicine for usual follow-up. Four studies used teleconferencing for usual postoperative care assessment and found that the technology enabled strong connectivity between patients and the healthcare provider ( 23 , 31 , 34 , 35 ). Two studies described the use of videoconferencing via a mobile phone for remote patient monitoring using an electronic blood pressure monitoring device or for monitoring surgical drains and found that it was very beneficial for both parties ( 26 , 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous experiences with telemedicine in postoperative care have demonstrated safe and effective wound care, postoperative patient education and even ileostomy output management [ 10 , 11 ]. However, most patients and providers prefer in-person postoperative visits during normal times [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…These data mostly came from patients' observation records in the hospital (including outpatient review) belonging to on-site data collection. Using remote video conference to evaluate ileostomy output, and taking early intervention measures to improve prognosis is a method worth exploring [23]. Multicenter, large sample randomized controlled studies of HOS should be conducted in the future.…”
Section: Discussionmentioning
confidence: 99%